Risk Factors Associated with Epilepsy among Children with Cerebral Palsy (Bangladesh Journal of Child Health, 2020)
Background: Cerebral Palsy(CP) is a major cause of childhood disability and is more prevalent in the more socioeconomically deprived populations of the world. Epilepsy is said to occur in 15-90% of children with CP and this causes additional economic and psychological stress on affected children and their family.Materials and Methods: This cross sectional case control study was conducted in paediatric neurology OPD of Dhaka Medical College Hospital & BSMMU from July 2008 to June 2009. Four hundred children with CP were included in this study & CP with epilepsy was taken as case and CP without epilepsy as control. Medical records of these patients were reviewed and analyzed.Results: 150 children studied had associated epilepsy, giving a prevalence rate of 37.5%. Epilepsy most commonly affected children with spastic quadriplegia (43.5%). GTCS was more common of epilepsy in spastic quadriplegic CP and partial seizure common in spastic hemiplegic CP. After logistic regression analysis significant positive correlation was found between LBW (OR, 0.428), post-natal CNS infection (OR, 0.416) with occurrence of epilepsy in CP cases. Statistically significant positive correlation was not found between prematurity, neonatal jaundice, neonatal convulsion, neonatal sepsis as a risk factor to develop epilepsy in CP.Conclusion: Among CP cases epilepsy is most common in spastic quadriplegic CP and GTCS is more common type of epilepsy in spastic quadriplegic CP. LBW and postnatal CNS infection significantly increase the risk of epilepsy in CP cases. Prematurity, neonatal jaundice, neonatal convulsion does not increase the risk of developing epilepsy in CP.Bangladesh J Child Health 2020; VOL 44 (2) :92-96